Staatliche Grenzen - Miggelbrink, Judith 1966- (Dialektik des Globalen. Kernbegriffe, 2019)
State borders are a central topos of political debates in Europe, in which liberal, national-conservative, populist and openly racist positions are articulated. What functions do they have? What effects and contradictions with regard to the control of which mobilities are produced by borders? These are the questions this volume explores